Countering the effects of urban green gentrification through nature-based solutions: A scoping review - Bressane, Adriano [UNESP]; Pinto, Joao Pedro da Cunha [UNESP]; Medeiros, Líliam César de Castro [UNESP] (Elsevier, 2024)
Statement of problem: Green gentrification is an emerging issue, where Urban green space (UGS) upgrades lead to higher living costs, displacing lower-income residents, raising concerns about accessibility, sustainability, and equity. This phenomena challenges the inclusive and equitable development of urban environments. Purpose: Through an integrative analysis of existing literature, this study aims to address a significant gap in current research by exploring how Nature-Based Solutions (NbS) can more effectively counteract the adverse effects of UGS gentrification. Method: Utilizing a scoping literature review, the research analyzes articles from 2015 to 2024 to synthesize insights for a more equitable urban development. Results: Findings reveal diverse lessons learned and strategies for countering green gentrification across different urban settings worldwide. However, a significant number of studies predominantly focus on the Global North, primarily in Europe and North America, which may lead to a regional bias. Practical implications: The results provide insights for policymakers, urban planners, and communities, guiding the creation of more inclusive and sustainable urban green spaces. Future directions: Further research should focus on developing quantitative metrics to evaluate the effectiveness of NbS in mitigating urban gentrification and expanding the geographic focus to include more underrepresented regions.
Keywords: Environmental justice; Green gentrification; Nature-based solutions; Review; Urban greening